UMPAN BENUA (UNGKAPAN UCAP SYUKUR MASYARAKAT SINTANG) - Meilania, Meilania; Ismunandar, Ismunandar; Djau, Nurmala Sari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractUmpan Benua is a piece of dance departs from community traditions in Sintang Regency. Umpan Benua is a term used by the Sintang community to refer to rituals, ceremonies or parties after the harvest. Umpan Benua traditional ritual was led by a traditional shaman who performed at the Balai Perangin Palace of the Sintang Sultanate Palace right in front of the Sintang Palace, beginning with the whole community deliberating. Ritual of Umpan Benua dance uses special tools that must be prepared such as seven Ancak Ancak (plaits made of bamboo 6 round shape and 1 boat shape) these seven ancak are a symbol where the ancak will later be offered or drowned in the Kapuas and Melawi rivers. Umpan Benua dance applies the methods and stages of creation in dance work including exploration, processing, application, evaluation, and revision. This is important because a writing process also requires a systematic work to facilitate writing so that it can run according to a predetermined conceptual framework.This presentation creates dance performance aesthetics in terms of both dance and musical accompaniment, so that this work is not only a spectacle, but also a work where the musical accompaniment is interesting to hear. Â Keywords: Umpanbenua dance, legend, production management, methods and stages of creation of presentation and analysis of works